Moins de biens pour plus de liens : Jean-Jacques Rousseau, décroissanciste avant l’heure ? - Pierre Crétois (Astérion)
Rousseau’s writings are far from the current developments of the capitalist economy, but they do foreshadow many of its consequences. The link between his philosophy and degrowth thinking illuminates both his approach and the genealogy of this economical tradition. Rousseau, by promoting a lifestyle of small and self-sufficient property owners, tries to avoid the logic of a commerce. His desire to tendentially suppress trade seems to have the primary aim of freeing human relationships from the constraints of selfish exchange so as to promote non-alienated relationships. We intend to show the link between Rousseau and contemporary degrowth theory by considering Émeline De Bouver’s expression “fewer goods, more relationships” as Rousseauan. The principle of “voluntary simplicity against the myth of abundance” animates the degrowth movement. The aim of the degrowth thinkers is to promote gratuity, non-commercial relationships against the logic of consumption and the commodification of all aspects of life and human relationships. Jean-Jacques Rousseau similarly seeks to reduce commercial exchange and promote a certain form of economic autarky. He does so not because he wants to suppress these exchanges, but in order to maintain intact the relations of confidence, friendship and intimacy, which he argues will be perverted if they are invaded by a logic of commercial exchange.